2018
DOI: 10.1186/s13690-018-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of business perspectives and tactics of tobacco and vape shop retailers in three communities in Orange County, CA, 2015–2016

Abstract: BackgroundIn response to the growing awareness and use of electronic nicotine delivery systems (ENDS), or e-cigarettes, the U.S. Food and Drug Administration asserted its regulatory authority over ENDS in May 2016. Federal, state, and local regulatory action on ENDS may have significant and unique impacts on specialty ENDS retailers, including tobacco and vape shops. The purpose of this study is to describe the commercial motivations of vape shops in minority communities as business entities whose financial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…We also observed that ‘vape enthusiasts’ and retailers were the most common channel who posted e-cigarette videos about product reviews and instructions, which is a novel way to promote e-cigarettes without using traditional paid ads that could be tracked and regulated. This finding is consistent with previous qualitative studies that observed that vape shop retailers considered social media as a new effective marketing channel to use strategies, such as featuring new e-cigarette products 28 29. We used the term ‘vape enthusiasts’ to refer to channels that primarily posted videos about e-cigarettes 30.…”
Section: Discussionsupporting
confidence: 85%
“…We also observed that ‘vape enthusiasts’ and retailers were the most common channel who posted e-cigarette videos about product reviews and instructions, which is a novel way to promote e-cigarettes without using traditional paid ads that could be tracked and regulated. This finding is consistent with previous qualitative studies that observed that vape shop retailers considered social media as a new effective marketing channel to use strategies, such as featuring new e-cigarette products 28 29. We used the term ‘vape enthusiasts’ to refer to channels that primarily posted videos about e-cigarettes 30.…”
Section: Discussionsupporting
confidence: 85%
“…Merchants’ perspectives regarding the implications of tobacco regulations provided valuable insights into shifts in the e-cigarette marketplace that will likely occur. In this sample of retailers, roughly half owned or managed vape shops that do not sell combustible tobacco products [ 6 ] and may advocate vaping to aid in cigarette cessation, despite such marketing being prohibited [ 38 , 55 ]. However, as a result of such regulations, many vape shops have faced—or are beginning to face—a difficult decision: struggle to survive, close, or rebrand with new inventory—which likely includes a wider variety of tobacco products [ 34 , 42 , 43 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the nicotine marketplace has evolved and key regulations have gone into effect that may substantially impact the vape retail environment and product use [ 34 ], understanding merchants’ perspectives regarding such regulations may have important implications for regulatory efforts [ 35 ]. For example, prior research involving vape retail merchants has provided unique insights into their marketing strategies [ 36 , 37 , 38 ], as well as into their concerns that policies are not distinguishing e-cigarettes from traditional tobacco (e.g., cigarettes) [ 39 , 40 , 41 ] and/or not taking into account the impact on the potential harm reduction that could result from using e-cigarettes [ 37 , 38 , 40 ]. As these more recent policies and regulatory changes (e.g., flavor restrictions, T21, COVID-19-related orders) have occurred, engaging the perspectives of vape retailers may provide unique insights into the future of vape products and retail.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, one might expect that smokers purchasing their NVPs from a vape shop would get better instruction on how to vape to maximize nicotine delivery compared to those purchasing their NVPs online or in a cigarette selling retail store. Additionally, since vape shops are typically not in the business of selling cigarettes or other tobacco products, there would be an incentive for the vape shop owners to encourage consumers to completely switch away from cigarettes [27]. On the other hand, vape shops remain unregulated, so it is unclear if consumers would get accurate information about the NVPs they are purchasing [28].…”
Section: Discussionmentioning
confidence: 99%